(untitled) (Hekima Review, 2009)
St Ignatius of Loyola, the founder of the Society of Jesus (Jesuits), left The Spiritual Exercises for the Church. It is a manual where he noted down his spiritual experiences for the purpose of those who may want to share in it. This manual forms the heart of what is called Ignatian spirituality. One of the hallmarks of the manual is the Election: a way of discerning and discovering God’s will for someone and what type of vocation God may be calling someone to. This hallmark is very central in The Spiritual Exercise that one can actually say that all the prayer exercises are geared towards making the right Election. This paper wants to meditate on the immediate preparation for the Election. My thesis is that Ignatius was very careful and smart in proposing exercises to ensure that anyone who follows the instructions will make a correct Election. The immediate preparation is centred on three things: Two Standards (2S), Three Types of Persons (3T) and Three Degrees of Humility (3D). This paper will scrutinize these concepts in details; explain their dynamics and how they set the stage for the act of Election. Since The Spiritual Exercise is meant to be done and not read, emphasis shall be laid on how to give the exercises on immediate preparation. Finally, since the fruits of the Exercises are coloured by personal history and experiences, I shall draw some insights from my own experience of these immediate preparations. This is done as an invitation to retreat directors to pay attention to the individual context of the retreatant who is trying to make the Election.